2020
DOI: 10.29252/mcs.7.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Effectiveness of Stress Inoculation Training on Nurses’ Job Stress at Selected Military Hospitals  

Abstract: Introduction: Since nursing is recognized as a stressful job, stresses caused by stressors in this profession can lead to diseases and disorders that seriously endanger the health of nurses. This study aims to help reduce nurses' job stress by using SIT (Stress Inoculation Training), one of the methods for stress reduction and management. Objective: This study aimed to determine the effectiveness of Stress InoculationTraining on nurses' job stress. Materials and Methods: The present study is a quasi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There is a dearth of literature discussing the use of SIT to reduce anxiety in nurses; however, two studies have used SIT for nurses to decrease stress. Both studies reported no significant effects of SIT on stress (Khatoni et al., 2020; Suryanto & Alfian, 2020). A 2016 systematic review examining the effects of SIT on post‐traumatic stress disorder (PTSD) found that SIT improved PTSD symptoms initially, but this waned over a 3‐month period (Lee et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is a dearth of literature discussing the use of SIT to reduce anxiety in nurses; however, two studies have used SIT for nurses to decrease stress. Both studies reported no significant effects of SIT on stress (Khatoni et al., 2020; Suryanto & Alfian, 2020). A 2016 systematic review examining the effects of SIT on post‐traumatic stress disorder (PTSD) found that SIT improved PTSD symptoms initially, but this waned over a 3‐month period (Lee et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Two earlier studies showed that teaching job coping strategies can reduce job stress (Ebert et al, 2016 ; Sohrabi et al, 2019 ). The results of the study of Khatoni et al showed that stress immunization training on the level of job stress of nurses working in selected military hospitals was not associated with a significant reduction in their job stress (Khatoni et al, 2020 ). Xu et al reported that the scores of PTG and its subscales were significantly higher after intervention (Xu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%